Chromatopia : an illustrated history of colour - Coles, David; Lander, Adrian (London : Thames & Hudson Ltd, 2019)
Did you know that the Egyptians created the first synthetic colour; or that the noblest purple comes from a predatory sea snail? Throughout history, artist pigments have been made from deadly metals, poisonous minerals, urine, cow dung, and even crushed insects. From grinding down beetles and burning animal bones to alchemy and serendipity, Chromatopia reveals the origin stories of over 50 of history's most extraordinary pigments. Spanning the ancient world to modern leaps in technology, this is a book for the artist, the history buff, the science lover and the design fanatic.
Includes bibliographical references (page 222).
Keywords: Color in art; Color in art; Color -- History; Color; Color; Colors -- History; Colors; Colors; History; History